Acute myeloid leukemia in a patient with constitutional 47, XXY karyotype. Issue 1 (2015) - Jalbut, Marla M.; Sohani, Aliyah R.; Cin, Paola Dal; Hasserjian, Robert P.; Moran, Jenna A.; Brunner, Andrew M.; Fathi, Amir T.
Abstract: Klinefelter syndrome (KS), a 47, XXY chromosomal abnormality, has been shown to be associated with a number of malignancies, but has not been linked to acute leukemias to date. We present a case of a 54-year-old male diagnosed with acute myeloid leukemia (AML) with monocytic differentiation, whose cytogenetic and subsequent FISH analyses revealed a constitutional 47, XXY karyotype. We also review and discuss relevant prior literature. Highlights: Constitutional 47, XXY is associated with increased risk for certain malignancies. There is no established association between 47, XXY (Klinefelter syndrome) and AML. We here report a case of AML in a patient with constitutional 47, XXY. A literature survey suggests that constitutional 47, XXY and AML occur uncommonly. Literature review suggests 47, XXY and AML are more often seen in younger patients.